HyBryte™ use in early-stage cutaneous T-cell lymphoma - Brian Poligone; Carolina V. Alexander-Savino; Ellen J. Kim; Aaron R. Mangold; Jennifer Desimone; Henry K. Wong; Adam T. Rumage; Oreola Donini; Andrea Haulenbeek; Christopher J. Schaber; Richard Straube; Christopher Pullion; et al. (Frontiers Media S.A., 2023)
Cutaneous T-cell lymphoma (CTCL) is a rare type of non-Hodgkin lymphoma of the skin, where at later stages skin-homing malignant T-cells affect lymph nodes, blood, and visceral organs. Even though early CTCL does not affect survival, it can progress to more advanced stages of disease and have a significant effect on the quality of life of patients. Although expectant management is a treatment consideration in early disease stages, most patients cycle through different skin-directed therapies throughout their lifetime. It can become a challenge to manage the serious and accumulating risk of side effects of these therapies, including various skin cancers and skin damage. Adverse effects from topical therapies limit their long-term utility. Thus, there is an unmet need for well-characterized therapies that have a rapid onset of action and minimal long-term/cumulative side effect profile. Most recently, the results of a Phase 3 study of topical HyBryte™ as a potential treatment for CTCL demonstrated its efficacy and safety profile. This article summarizes what is known about HyBryte™, focuses on its mechanism of action, and highlights its effectiveness, safety, and tolerability in the context of other current FDA-approved topical therapies for CTCL.